Utilization of fuzzy b-pline for three-dimensional tsunami wave reconstruction from quickbird satellite data - Marghany, Maged; Hashim, Mazlan (2008)
Fuzzy B-spline based on frequency domain is utilized to reconstruct three-dimensional (3D) successive tsunami waves from Quickbird satellite data. In doing so, two-dimensional Fourier transform (2DFFT) is used to retrieve characteristics of tsunami wave spectra i.e. frequency, wavelength, direction and energy. Thus, fuzzy B-spline is implemented to reconstruct a global topographic structure between the data points were used to support an approximation to the real successive tsunami wave propagations and run-up. The result show the 3D visualization of tsunami wave propagation in which to be the most satisfactory. The maximum tsunami wave height is 6 m which is clearly noticed along along Kalutara coastline.